2019
DOI: 10.1016/j.ijhm.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The dimensions of hotel customer ratings that boost RevPAR

Abstract: Online ratings provide valuable information to operators. However, the use of this information for revenue maximization purposes remains at a moot point. This article proposes a new method to decompose ratings based on their relevance to hotel performance. From a methodological standpoint, we propose a multi-criteria decision analysis approach. The empirical validation includes two independent data sources, online ratings from Booking.com and RevPAR data from STR. By means of pairwise comparisons in PROMETHEE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 65 publications
0
24
0
2
Order By: Relevance
“…Also, (Öğüt & Onur Taş, ) found that 84% of all hotel guests use online reviews to help them plan their holidays. Furthermore, Nieto‐Garcia, Resce, Ishizaka, Occhiocupo, and Viglia () and Viglia, Minazzi, and Buhalis () argue that hotel managers should strive to understand the effect of consumers' attitude to online reviews on their decision making and in turn hotel performance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, (Öğüt & Onur Taş, ) found that 84% of all hotel guests use online reviews to help them plan their holidays. Furthermore, Nieto‐Garcia, Resce, Ishizaka, Occhiocupo, and Viglia () and Viglia, Minazzi, and Buhalis () argue that hotel managers should strive to understand the effect of consumers' attitude to online reviews on their decision making and in turn hotel performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the usage of specific software to process large databases is crucial for the success of RM (Guadix et al, 2010; Hormby et al, 2010). The intersection between online ratings and revenue maximization is also confirmed (Nieto-Garcia et al, 2019). Xu et al (2019) advocated that, for hotels to better understand guests’ needs and forecast future demand, online customer reviews should be utilized, and accurate records of past customer demand and room occupancy should be kept.…”
Section: Literature Reviewmentioning
confidence: 66%
“…Along with the fruition of tourism studies during these years, hospitality research reached high altitudes. Academicians invested their resources in understanding consumer perception about hospitality services provided by hotels (Perez-Aranda et al, 2018), the role of rating systems (Gavilan et al, 2018; Nieto-Garcia et al, 2019), consumer reviews in hotel bookings (Tsao et al, 2015) and customer satisfaction and loyalty about hospitality services (Serra & Salvi, 2014). Further, eWOM studies during this tenure have been conducted on diverse eWOM platforms like social media (Tan & Lee, 2019), online reviews (Matute et al, 2016), blogs (Gvili & Levy, 2018) and discussion forums (Shih et al, 2013).…”
Section: Resultsmentioning
confidence: 99%